مدى إدراك مديري المنظمات العامة في الساحل السوري لمفهوم الإدارة الإلكترونية دراسة ميدانية - ناصر, محمد; ديوب, علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتمحور هذه الدراسة حول تحديد مدى إدراك مديري المنظمات العامة لمفهوم الإدارة الإلكترونية وتطبيقاته المختلفة، وذلك من خلال تحديد العوامل المؤثرة على اعتماد نظام الإدارة الإلكترونية وتطبيقاته المختلفة من قبل المنظمات العامة في الساحل السوري، وإمكانية تعميم ذلك على الجمهورية العربية السورية. وتوضح أن استمرار مدراء المنظمات العامة في إدارة منظماتهم بالأساليب الإدارية التقليدية وعدم اعتمادهم نظام الإدارة الإلكترونية يكرس البطء في إنجاز كافة المعاملات وسوء تنفيذها، كما يمثل تفريطاً بالفرص الكثيرة الواعدة من تطبيق هذا النظام، وبالتالي يساهم في عدم قدرة هذه المنظمات على الاستغلال الأمثل لمواردها الاقتصادية والاجتماعية بما يمكنها من تحقيق أهدافها المنشودة في البقاء والنمو والازدهار . وتقوم هذه الدراسة على اعتماد المنهج الوصفي التحليلي الذي من خلاله تم التوصل إلى النتائج التالية: أ-عدم اعتماد معظم مديري المنظمات العامة على نظام الإدارة الإلكترونية, الأمر الذي أدى إلى إخفاقهم في إدارة منظماتهم وتوجيهها نحو الارتقاء والازدهار . ب-هنالك ضعف واضح في البنى التحتية لتكنولوجيا المعلومات والاتصالات, وهذا ما يقف عائقاً في وجه تطبيق الإدارة الإلكترونية . ج-يوجد العديد من مدراء المنظمات العامة السورية يفتقرون للمهارات التي تتطلبها تطبيق الإدارة الإلكترونية. هـ-إن اعتماد نظام الإدارة الإلكترونية وتطبيقه في المنظمات العامة سوف يؤدي بالتأكيد إلى تحسين مستوى أداء هذه المنظمات ويعزز من مكانتها, ويفسح أمامها مجالاً واسعاً لاغتنام العديد من الفرص الواعدة . This study focuses on defining the extent of perception of the general organizations directors of the concept of electronic management and its different applications by determining the elements that affect the adoption of such electronic management system. It also aims at identifying its different applications by different general organizations in the Syrian Coast , and checking the possibility of generalizing such application in the Syrian Arab Republic. The study shows that the continuous use of traditional management methods , and not adopting the electronic management system, increases the slowness in performing all transactions and results in bad execution. Such old-fashioned methods represent a misuse of the numerous promising chances of applying this system, something that makes these organizations unable to do the optimal exploitation of their economic and social recourses to achieve their desired goals in maintenance , growth and prosperity . This study is based on the adoption of the descriptive analytic method through which the following results have been reached : 1. Most managers of the general organizations do not depend on the electronic management system, a thing which led to their failure in managing their organizations and directing them towards progress and prosperity. 2. There is a clear weakness in the infrastructures of the information and communication technology. This puts an obstacle in the face of the application of electronic management . 3. There are many managers of the Syrian general organizations who lack the skills required to apply the electronic management. 4. The adoption of the electronic management and its application in the general organizations will certainly lead to the improvement and enhancement of the level of performance. It opens new horizons to take advantage of such numerous promising chances.